2014
DOI: 10.1164/rccm.201405-0850oc
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Transfusion of Stored Red Blood Cells Increases Pulmonary Artery Pressure

Abstract: Rationale: Transfusion of erythrocytes stored for prolonged periods is associated with increased mortality. Erythrocytes undergo hemolysis during storage and after transfusion. Plasma hemoglobin scavenges endogenous nitric oxide leading to systemic and pulmonary vasoconstriction.Objectives: We hypothesized that transfusion of autologous blood stored for 40 days would increase the pulmonary artery pressure in volunteers with endothelial dysfunction (impaired endothelial production of nitric oxide). We also test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 36 publications
5
65
2
1
Order By: Relevance
“…This hemodynamic response in HFSD guinea pigs was associated with Hb-induced expression of inactive eNOS (Supplemental Figure 1; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.93577DS1). These characteristics mimic a frequent cardiovascular comorbidity found in patients undergoing blood transfusion (26).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…This hemodynamic response in HFSD guinea pigs was associated with Hb-induced expression of inactive eNOS (Supplemental Figure 1; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.93577DS1). These characteristics mimic a frequent cardiovascular comorbidity found in patients undergoing blood transfusion (26).…”
Section: Resultsmentioning
confidence: 55%
“…The vulnerability of mice (24,25,32), lambs (15), and patients (26) with endothelial dysfunction to the pathophysiological effects of Hb and RBC transfusion has been established by Zapol and colleagues. This group has also convincingly demonstrated that maximally stored RBCs (42-day equivalent) caused a poor resuscitation response in a mouse model of shock (24,25) and a significant increase in pulmonary arterial pressure in obese volunteers (26).…”
Section: Discussionmentioning
confidence: 96%
“…In animals, inducing intravascular hemolysis or infusing hemoglobin or hemolysate can produce experimental NO resistance (86)(87)(88)(89). This effect is attributable to hemoglobin and NO scavenging, as it can be blocked by oxidization of hemoglobin to methemoglobin with inhaled NO gas or by binding and clearance of hemoglobin with haptoglobin (86,(89)(90)(91). Acute intravascular hemolysis induced by hypotonic water infusion in mice inhibits NO signaling and causes inflammation, an effect phenocopied by acute NO inhibition using chemical NO scavengers and reversed by an NO donor and haptoglobin (92).…”
Section: Ph and Mortality In Scdmentioning
confidence: 99%
“…Infusing aged stored blood into rodents (89,93,94) and humans (90,95) causes intravascular hemolysis, pulmonary and systemic hypertension, and vascular endothelial dysfunction (due to impaired NO signaling) that can be blocked by haptoglobin (96). These effects are not always observed in models or patient populations in which hemolysis is not as severe, the dose of transfused red cells is not large, and the existing compensatory reserves of haptoglobin, hemopexin, and catalytic antioxidants are not as chronically depleted as in SCD.…”
Section: Ph and Mortality In Scdmentioning
confidence: 99%
“…However, in these studies the mean ages of older blood were only 22 and 28.3 days, respectively, and very few units of blood were transfused at the extreme limits of FDA-approved storage of 42 days (16)(17)(18). Thus, although transfusion of blood may increase risk (12,13,15,19), whether this risk is compounded by storage age, especially at the limits of storage and in the setting of larger transfusion volumes, remains unclear (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%